Systemic Risk, Aggregate Demand, and Commodity Prices - Gomez-Pineda, Javier; Guillaume, Dominique; Tanyeri, Kadir (Washington, D.C. : International Monetary Fund, 2015)
The paper presents a global model with systemic and country risks, as well as commodity prices.We show that systemic risk shocks have an important impact on world economic activity, with the busts in world output gap corresponding to unobserved systemic risk associated with major financial events. In addition, systemic risk shocks are shown to be important drivers of output gaps while country risk premium shocks can have important effects on the trade balance. Commodity prices, in particular the price of oil, are shown to be demand driven. The model performs well at one- and four-quarter horizons compared to a survey of analysts' forecasts. In addition, systemic risk shocks explain a large share of the forecast variance for the world output gap, country output gaps, the price of oil, and country risk premiums. The importance of systemic risk shocks lends support for financial surveillance with a systemic focus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet